CD38 marks the exhausted CD8+ tissue-resident memory T cells in hepatocellular carcinoma - Reolo, Marie J. Y.; Otsuka, Masayuki; Seow, Justine Jia Wen; Lee, Joycelyn; Lee, Yun Hua; Nguyen, Phuong H. D.; Lim, Chun Jye; Wasser, Martin; Chua, Camillus; Lim, Tony K. H.; Leow, Wei Qiang; Chung, Alexander; et al. (Frontiers in Immunology, 2023)
Hepatocellular carcinoma (HCC) is one of the most common liver cancers and the third leading cause of cancer death globally. Despite recent advances in immunotherapy for HCC, the overall modest response rate underscores the need for a better understanding of the tumor microenvironment (TME) of HCC. We have previously shown that CD38 is widely expressed on tumor-infiltrating leukocytes (TILs), predominantly on CD3+ T cells and monocytes. However, its specific role in the HCC TME remains unclear. In this current study, we aim to bridge this gap by understanding the involvement of CD38 in the TME of HCC through comprehensive multidimensional immunoprofiling. Using cytometry time-of-flight (CyTOF) analysis, we compared the immune composition of CD38-expressing leukocytes in TILs, non-tumor tissue-infiltrating leukocytes (NIL), and peripheral blood mononuclear cells (PBMC). We identified CD8+ T cells as the dominant CD38-expressing TILs and found that CD38 expression was significantly higher in CD8+ TRM in TILs than in NILs. Furthermore, through transcriptomic analysis on sorted CD8+ TRM from HCC tumors, we observed a higher expression of CD38 along with T cell exhaustion genes, including PDCD1 and CTLA4, compared to the circulating memory CD8 T cells from PBMC. This was validated by single-cell RNA-sequencing that revealed co-expression of CD38 with PDCD1, CTLA4, and ITGAE (CD103) in T cells from HCC tumors. The protein co-expression of CD38 and PD-1 on CD8+ T cells was further demonstrated by multiplex immunohistochemistry (mIHC) on HCC FFPE tissues, marking CD38 as a T cell co-exhaustion marker in HCC. Lastly, the higher proportions of CD38+PD-1+CD8+ T cells and CD38+PD-1+ TRM were significantly associated with the higher histopathological grades of HCC, indicating its role in the aggressiveness of the disease. Taken together, the concurrent expression of CD38 with exhaustion markers on CD8+ TRM underpins its role as a key marker of T cell exhaustion and a potential therapeutic target for restoring cytotoxic T cell function in HCC.